2010
DOI: 10.1007/s10509-010-0528-2
|View full text |Cite
|
Sign up to set email alerts
|

Mass density of the upper atmosphere derived from Starlette’s Precise Orbit Determination with Satellite Laser Ranging

Abstract: The atmospheric mass density of the upper atmosphere from the spherical Starlette satellite's Precise Orbit Determination is first derived with Satellite Laser Ranging measurements at 815 to 1115 km during strong solar and geomagnetic activities. Starlette's orbit is determined using the improved orbit determination techniques combining optimum parameters with a precise empirical drag application to a gravity field. MSIS-86 and NRLMSISE-00 atmospheric density models are compared with the Starlette drag-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The principle of the LLR observations is well documented (Murphy 2013;Murphy et al 2012). Besides the lunar applications, the laser ranging technique is still intensively used for tracking Earth orbiting satellites, especially for very accurate orbital (Peron 2013;Lucchesi et al 2015) and geophysical studies (Matsuo et al 2013;Jeon et al 2011).…”
Section: Lunar Laser Rangingmentioning
confidence: 99%
“…The principle of the LLR observations is well documented (Murphy 2013;Murphy et al 2012). Besides the lunar applications, the laser ranging technique is still intensively used for tracking Earth orbiting satellites, especially for very accurate orbital (Peron 2013;Lucchesi et al 2015) and geophysical studies (Matsuo et al 2013;Jeon et al 2011).…”
Section: Lunar Laser Rangingmentioning
confidence: 99%
“…The estimation of the atmospheric drag coefficient could be found with various intervals. The frequency of the estimation of the atmospheric drag coefficient affected the accuracy of the orbit estimation results [ 8 , 9 , 34 , 35 ]. The atmospheric drag coefficient was estimated at intervals of 1, 2, 8, 12, and 24 h in the research.…”
Section: Short-arc Orbit Estimation With the Optical Observation Dmentioning
confidence: 99%
“…5 and 6, we determined the uncertainties in the conductivity and the EEF associated with the empirical model outputs in order to precisely determine the confidence limit in their magnitude. Although a large number of works deal with the comparisons between neutral atmosphere data and MSIS model prediction (Richards 2002;Liu et al 2005;Burke et al 2007;Park et al 2008;Jeon et al 2011), observed ionospheric data and IRI model predictions Batista et al 1996;de Souza et al 2003;Sethi et al 2004;Bertoni et al 2006;Lühr and Xiong 2010;Kenpankho et al 2011;Oyekola and Fagundes 2012;Yue et al 2013;Kumar et al 2014Kumar et al , 2015, and geomagnetic field data and IGRF predictions (Lowes 2000;Lowes and Olsen 2004), uncertainties (or potential errors) of these empirical models have not been published, even in Bilitza and Reinisch (2008), Picone et al (2002), and Finlay et al (2010).…”
Section: Analysis Of Linear Fittingmentioning
confidence: 99%